Does space finally matter? The Position of New Economic Geography in Economic Journals - Patrick Lehner; Gunther Maier (European Regional Science Association (ERSA), 2001)
This paper discusses recent developments in economics, like endogenous growth theory, new economic geography, networking theory, etc. and analyzes their implications for spatial structure. The paper presents the basic components of these theories and points out their communalities. This shows that all these theories are based on assumptions that lead to spatial structure, i.e. differences in the spatial allocation of econimic activities. This structure in turn represents an important basis for the argumentation of these new developments in economic theory. Although they rarely make this explicit, many economists in recent years have build models that produce as a by-product spatial structure. It is argued in this paper that economics has reached a state where spatial structures and regional differences can no longer be ignored, because they have become an integral part of core economic theories in recent years.
Keywords: 330